THE INFLUENCE OF CAREGIVERS' SLEEP, BURDEN, COPING, AND CARE-RECIPIENTS' SLEEP ON CAREGIVERS' HEALTH. (11th November 2018) - Chang, Y; Peng, H
Abstract: Family caregivers often take primary responsibility and manage all aspects of the care for their care-recipients with dementia so are at high risk of experiencing physical and mental health issues. Family caregivers with uncontrolled symptoms might demonstrate poor health outcomes and low quality of life. The study aimed was to examine the influence of caregivers' sleep, caregiver burden, caregiver coping, and care recipient's sleep on caregivers' physical and mental health. This study used a cross-sectional design. Measures used in this study included Pittsburgh Sleep Quality Index (PSQI), Actiwatch (wore for 7 days), Caregiver Burden Inventory (CBI), the COPE inventory, Sleep Disorder Index (for care-recipient's sleep). Caregivers' health was measured by the 12-item Short Form Health Survey (SF-12) including physical and mental health. Descriptive statistics and regression analysis were used for data analysis. Forty-five family caregivers participated in this study. The results of regression analysis indicated that caregivers' sleep, burden, coping, and care recipient's sleep were significant predictors of caregivers' mental health and the model explained the 83.2 % of the total variance. Caregivers' sleep, burden, and care recipient's sleep were significant predictors of caregivers' physical health and the model explained the 70.4% of the total variance. Our findings provide important information regarding the impact of caregivers' and care-recipients' sleep on caregivers' physical and mental health. Clinicians should routinely evaluate sleep quality in family caregivers and their care-recipients with dementia. Interventions should include components designed to improve caregivers' and care-recipients' sleep quality which have great potential to improve caregivers' health.